Responding to change: Learning to adapt in development cooperation - Engel, Paul; Keijzer, Niels; Ørnemark, Charlotte (Policy Management Brief 19, 2007)

The high cost of accurate knowledge - Sutcliffe, Kathleen M.; Weber, Klaus (Harvard Business Review, 2003)
Many business thinkers believe it's the role of senior managers to scan the external environment to monitor contingencies and constraints, and to use that precise knowledge to modify the company's strategy and design. As these thinkers see it, managers need accurate and abundant information to carry out that role. According to that logic, it makes sense to invest heavily in systems for collecting and organizing competitive information. Another school of pundits contends that, since today's complex information often isn't precise anyway, it's not worth going overboard with such investments. In other words, it's not the accuracy and abundance of information that should matter most to top executives--rather, it's how that information is interpreted. After all, the role of senior managers isn't just to make decisions; it's to set direction and motivate others in the face of ambiguities and conflicting demands. Top executives must interpret information and communicate those interpretations--they must manage meaning more than they must manage information. So which of these competing views is the right one? Research conducted by academics Sutcliffe and Weber found that how accurate senior executives are about their competitive environments is indeed less important for strategy and corresponding organizational changes than the way in which they interpret information about their environments. Investments in shaping those interpretations, therefore, may create a more durable competitive advantage than investments in obtaining and organizing more information. And what kinds of interpretations are most closely linked with high performance? Their research suggests that high performers respond positively to opportunities, yet they aren't overconfident in their abilities to take advantage of those opportunities.
Keywords: Administrative Personnel; Data Collection; Decision Making, Organizational; Economic Competition; Information Management; Investments; Marketing; Organizational Innovation; United States

Learning in the Thick of It - Darling, Marilyn; Parry, Charles; Moore, Joseph (Harvard Business Review, 2005)
After-action reviews identify past mistakes but rarely enhance future performance. Companies wanting to fully exploit this tool should look to its master: the U.S. Army’s standing enemy brigade, where soldiers learn and improve even in the midst of battle.
Keywords: Aerospace sector; Corporate governance; Decision making and problem solving; Defense industry; Defense sector; Fabrication and manufacturing; Meeting management; Military; North America; Organizational culture; Presentation skills; Project management; Psychology; Telecom

Outcome Mapping: Building Learning and Reflection into Development Programs - Earl, Sarah; Carden, Fred; Smutylo, Terry; Patten, Michael Quinn (IDRC Books, 2001)
"Outcome Mapping provides not only a guide to essential evaluation map-making, but also a guide to learning and increased effectiveness, and affirmation that being attentive along the journey is as important as, and critical to, arriving at a destination." - Michael Quinn PattonMore and more, development organizations are under pressure to demonstrate that their programs result in significant and lasting changes in the well-being of their intended beneficiaries. However, such "impacts" are often the product of a confluence of events for which no single agency or group of agencies can realistically claim full credit. As a result, assessing development impacts is problematic, yet many organizations continue to struggle to measure results far beyond the reach of their programs. "Outcome Mapping" recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, "Outcome Mapping" debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in terms of the results it achieves. This publication explains the various steps in the outcome mapping approach and provides detailed information on workshop design and facilitation. It includes numerous worksheets and examples.

Donors' Learning Difficulties: Results, Relationships and Responsibilities - Eyben, Rosalind (IDS Bulletin, 2005)